Histomorphometric and Immunohistochemical Study of Early Adaptative Response of the Vascular Wall in a Termino-Terminal Microsurgical Model of Femoral Vessels in Wistar Rat - Velázquez Gauna, Sergio Everardo; Soto Domínguez, Adolfo; Quiroga Garza, Alejandro; Reyes Hernández, Cynthia Guadalupe; Chávez Reyes, Arturo; Morales Avalos, Rodolfo; Montes de Oca Luna, Roberto; Guzmán López, Santos; Elizondo Omaña, Rodrigo Enrique (2017)
SUMMARY: When a vein segment is grafted into arterial circulation, biomechanical forces stimulate modification of its structure. This morphological adaptive response is progressive during a medium or long term and occludes the vessel lumen, leading to a graft failure. The objective of this study was to characterize the early morphological response of the vascular wall in a terminal-terminal vascular vein graft model in Wistar rats. A segment of the femoral vein was placed in the femoral circulation. An end to end microsurgical graft anastomosis technique was implemented and standardized in twenty rats. The samples were processed with histological technique to analyze the overall structure with hematoxylin and eosin, the composition of the vessel wall with Masson trichrome technique, the proliferating and smooth muscle cells were detected with immunohistochemistry (anti-PCNA, anti-actin and anti CD68) and the induction of apoptosis with TUNEL technique. The times periods studied were 1, 3 and 5 days postoperative. There is progressive increase of cell proliferation and intensity of the density detected by PCNA with its peak at postoperative day 3. Apoptosis was not evident in any of the postoperative days. Smooth muscle had no significant change in any of the time periods studied. Macrophage and leukocyte migration was evident since the first postoperative day with infiltration into the media by the 5th day. This study characterizes the morphological aspects in the early arterialization of the vascular wall in a vein graft process. These results contribute to a better understanding of the morphopathological mechanism involved in vein graft failure. KEY WORDS: Hyperplasia; Morphology; Microsurgical model; Vascular adaptive changes; Venous graft.